(untitled) (Global Journal of Human-Social Science, 2023)
Rereading Little Women by Lousia May Alcott, an enduring classic in American literary history, the present essay argues that Mrs. March, as a moderate feminist drawing much from the transcendental thoughts about individualism, parents her daughters with empathy and care, while acknowledging the limitations of gender roles in the mid-19th century New England context. The March girls undergo journeys of growth, coping with negative emotions related to class and gender, and developing individual personalities under their mother’s guidance. Mrs. March’s empathic parenting leaves a lasting impact on her daughters, empowering them to navigate the complexities of their world and embrace their true selves with strength, compassion, and love.